'My relationships have changed because I've changed': biographical disruption, personal relationships and the formation of an early menopausal subjectivity. Issue 7 (25th June 2020) - Johnston‐Ataata, Kate; Flore, Jacinthe; Kokanović, Renata; Hickey, Martha; Teede, Helena; Boyle, Jacqueline A; Vincent, Amanda
Abstract: Early menopause (EM) or premature ovarian insufficiency (POI) can disrupt gendered and age‐related expectations associated with perceived 'normative' biographies for young adult women, with implications for subjectivity and relationships. While previous qualitative research has concentrated on the impacts of EM/POI on biography and sense of self, in this article, we examine the enmeshment of personal relationships with the formation of early menopausal subjectivities. Drawing on research exploring concepts of 'biographical disruption' and personal relationships, and theoretical work on social norms and subject formation, we present findings from a narrative thematic analysis of 25 interviews with women diagnosed with spontaneous or medically induced EM/POI. We identify three main narrative 'types' of subjective and relational experience in response to the 'disruption' of EM/POI: interlude and continuity; disruption and adaptation; and disruption and ambivalence. Women's accounts of their experience of EM/POI indicate that the formation of early menopausal selves is mediated by the extent to which women and those around them identify with gendered norms related to reproduction and age. Consistent with theoretical perspectives that consider the self as relationally produced, we argue that the subjective and relational dimensions of EM/POI are intertwined and must be understood in tandem.